Lesion localization and performance on Theory of Mind tests in stroke survivors: a systematic review (Archives of Clinical Psychiatry, 2020)
Background: Theory of Mind (ToM) is the ability to attribute mental states to oneself and others. Individuals with a brain lesion following a stroke exhibit a compromised ability to perform ToM tasks. Objective: To analyze studies that evaluated ToM in stroke survivors considering the lesion localization and performance on ToM tests. Methods: The searches were carried out until November 28, 2018, using the following search terms: “social cognition” or “Theory of Mind” and “stroke”. Searches were conducted in the PubMed, PsycInfo, Web of Science and Scopus data bases. The initial search led to the retrieval of 425 articles. After the exclusion of duplicates and the analysis of the titles, abstracts and full texts, 20 articles were selected for the present review. Results: The studies showed that patients with lesion in the right hemisphere present lower performance on ToM tasks compared to those with lesion in the left hemisphere. In addition, patients with lesion in the right hemisphere presented significant impairment in the performance on ToM tasks compared to healthy individuals. Furthermore, the studies that evaluated lesions in specific regions such as temporal lobe, prefrontal cortex, posterior parietal cortex, and temporo-parietal junction, indicated a significant deficit in ToM performance of these patients compared to healthy individuals. Discussion: This review showed that stroke survivors have a poor performance on ToM tasks. The right hemisphere and prefrontal cortex seem to be associated with the deficit of this ability.